EFL Secondary Students' Affective Engagement on Teacher Written Corrective Feedback in Biography Writing Class - Septian Garin Purnomo; Muhammad Reza Pahlevi (Journal of English Language and Education, 2021)
Research about students’ affective engagement in teacher written corrective feedback in EFL classroom has not given enormous concern. Therefore, this present study focuses on investigating students’ affective engagement towards teacher written corrective feedback. Case study was used as the research design. Four high school students involved in this research. Data were collected from multiple resources, including semi-structured interview and documentation. Thematic analysis was used to analyze the obtained data. The findings revealed that students’ affective engagement towards teacher written corrective feedback include students’ emotional involvement in curious learning activity, teacher written corrective feedback perceived by students in balance emotion- feeling of happiness and sadness, and teacher written corrective feedback stimulates students to engage cognitively.